HIMPUNAN DOMINASI SISI-SISI KUAT DAN SISI-SISI LEMAH DARI SUATU GRAF - Mutmainnah Mutmainnah (Jurnal Matematika, 2016)
ABSTRACT. Edge  e-dominates an edge  if  with  is the subgraph induced . A set  is an edge-edge domination set notated by EED-set if every edge in   is e-dominated by an edge in . The edge-edge domination number notated by  is the cardinality of a minimum EED-set. A set  is a strong edge-edge domination set notated by SEED-set if every edge in  is e-dominated strongly by an edge in  with the condition  and . Strong edge-edge domination number notated by . A set  is a weak edge-edge domination set notated by WEED-set if every edge in  is e-dominated weakly by an edge in  with the condition  and . Weak edge-edge domination number notated by . This final project we study about strong edge-edge domination set, weak edge-edge domination set and application edge-edge domination set namely determining the optimal number of security personnel that will be used to secure an area.